Augmented Reality: A Pleasure or a Pain? - Shepherd, William; Fishwick, Lee; Crighton, David; Starkie, Sean (PRISM: Casting New Light on Learning, Theory and Practice, 2019)
The following is a post-research discussion that reviews the findings of an action research project into Augmented Reality (AR) in the classroom.